Bather Shedding as a Source of Human Fecal Markers to a Recreational Beach - Li, Dong; Van De Werfhorst, Laurie C.; Steets, Brandon; Ervin, Jared; Murray, Jill L. S.; Devarajan, Naresh; Holden, Patricia A. (Frontiers in Microbiology, 2021)
Microbial source tracking (MST) can identify and locate surf zone fecal indicator bacteria (FIB) sources. However, DNA-based fecal marker results may raise new questions, since FIB and DNA marker sources can differ. Here, during 2 years of summertime (dry season) MST for a Goleta, California recreational beach, surf zone FIB were mainly from gulls, yet low level human-associated DNA-based fecal marker (HF183) was detected. Watershed sources were hypothesized because dry weather creek waters had elevated FIB, and runoff-generating rain events mobilized human (and dog) fecal markers and Salmonella spp. into creeks. However, the dry weather estuary outlet was bermed in the first study year; simultaneously, creek fecal markers and pathogens were lower or similar to surf zone results. Although the berm breached in the second year, surf zone fecal markers stayed low. Watershed sediments, intertidal beach sands, and nearshore sediments were devoid of HF183 and dog-associated DNA markers. Based on dye tests and groundwater sampling, beach sanitary sewers were not leaking; groundwater was also devoid of HF183. Offshore sources appeared unlikely, since FIB and fecal markers decreased along a spatial gradient from the surf zone towards nearshore and offshore ocean waters. Further, like other regional beaches, surf zone HF183 corresponded significantly to bather counts, especially in the afternoons when there were more swimmers. However, morning detections of surf zone HF183 when there were few swimmers raised the possibility that the wastewater treatment plant (WWTP) offshore outfall discharged HF183 overnight which transported to the surf zone. These findings support that there may be lowest achievable limits of surf zone HF183 owing to several chronic and permanent, perhaps diurnal, low concentration sources.